2019
DOI: 10.3390/foods8030097
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Chronology of Expression of Ten Extracellular Matrix Molecules during the Myogenesis in Cattle to Better Understand Sensory Properties of Meat

Abstract: The sensory properties of beef are known to depend on muscle fiber and intramuscular connective tissue composition (IMCT). IMCT is composed of collagens, proteoglycans and glycoproteins. The differentiation of muscle fibers has been extensively studied but there is scarcity in the data concerning IMCT differentiation. In order to be able to control muscle differentiation to improve beef quality, it is essential to understand the ontogenesis of IMCT molecules. Therefore, in this study, we investigated the chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…1 PGs have an important role in tissue architecture and function by interacting with several collagen and noncollagen components and also with water molecules to create a water compartment. 7 From these properties, a few studies have suggested that PGs could contribute to meat texture, [8][9][10][11] although only two studies have investigated their relationship with beef tenderness. 6,12 Marbling, also called intramuscular fat content (IMF), develops inside IMCT during the fattening period of the animals.…”
Section: Introductionmentioning
confidence: 99%
“…1 PGs have an important role in tissue architecture and function by interacting with several collagen and noncollagen components and also with water molecules to create a water compartment. 7 From these properties, a few studies have suggested that PGs could contribute to meat texture, [8][9][10][11] although only two studies have investigated their relationship with beef tenderness. 6,12 Marbling, also called intramuscular fat content (IMF), develops inside IMCT during the fattening period of the animals.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of age at weaning and the cross-sectional area of the fibers in the prediction of tenderness may be explained by two reasons. First, it is known that animal growth affect muscle development and consequently its composition including connective tissue [46], evaluated in this study by collagen content and solubility. Second, animal growth had important consequences on protein turnover know to influence the final qualities of meat [47].…”
Section: Resultsmentioning
confidence: 99%
“…In the fourth topic dealing with muscle biochemistry and proteomics techniques, two original and independent papers are published [14,15]. The study by Zhu et al [14] assess the usefulness of RNAlater ® , regarded as a potential preservation method for proteins, to preserve post-mortem bovine muscle proteins compared with dry ice in a proteomic study.…”
mentioning
confidence: 99%
“…The results demonstrate that RNAlater ® can be a simple and efficient way to preserve bovine muscle proteins for meat proteomics, where snap-freezing may not be a viable option for sample stabilization. The second study by Listrat et al [15] deals with a deeper understanding of the ontogenesis of intramuscular connective tissue composition that would allow the control of muscle differentiation to improve beef quality. Therefore, the authors investigate the chronology of expression of ten extracellular matrix molecules in bovine Semitendinosus muscle using an immunohistology technique at five key stages of myogenesis.…”
mentioning
confidence: 99%